2017
DOI: 10.1002/2327-6924.12504
|View full text |Cite
|
Sign up to set email alerts
|

Biology of obesity and weight regain

Abstract: Background and purpose Weight loss is recommended as first‐line therapy for many chronic illnesses, including obesity. Most patients who do successfully lose weight are unable to maintain their reduced weight. Recent research findings are reviewed and synthesized to explain the biology of obesity, adaptation to weight loss, and weight regain. Findings Weight regain is a common consequence of successful weight loss. Current obesity management strategies fail to take into consideration the underlying genetic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 98 publications
0
4
0
Order By: Relevance
“…20,73,74,75 Many individuals regain weight after obesity treatment, 95,96 leading to concern about weight cycling. 75,97 Early research indicated patterns of weight loss and regain are associated with higher all-cause mortality and morbidity from cardiovascular disease; however, much of this research did not control for unintentional weight loss from underlying health conditions. [98][99][100][101] More recent findings support that treatments for obesity produce significant and sustained physical and mental health improvements, despite potential weight regain, and challenge the notion that losing and regaining causes more harm than never losing weight.…”
Section: Supervised Evidence-based Obesity Treatmentmentioning
confidence: 99%
“…20,73,74,75 Many individuals regain weight after obesity treatment, 95,96 leading to concern about weight cycling. 75,97 Early research indicated patterns of weight loss and regain are associated with higher all-cause mortality and morbidity from cardiovascular disease; however, much of this research did not control for unintentional weight loss from underlying health conditions. [98][99][100][101] More recent findings support that treatments for obesity produce significant and sustained physical and mental health improvements, despite potential weight regain, and challenge the notion that losing and regaining causes more harm than never losing weight.…”
Section: Supervised Evidence-based Obesity Treatmentmentioning
confidence: 99%
“…Being overweight and obese is caused by imbalances in intake coming from production (Rogge & Gautam, 2017;Sjarif et al, 2011). In this case, physical activity requires energy to move the body and skeletal muscles.…”
Section: Introductionmentioning
confidence: 99%
“…Obesity is a chronic multifactorial disorder of excess lipid accumulation in adipose tissue and ectopic sites, such as skeletal muscle and liver. It is generally caused by environmental factors and genetic predisposition ( 1 ). Diet and physical exercise are the primary treatment methods for obesity, and drug therapy is used if the first two methods are unsuccessful within the first six months.…”
Section: Introductionmentioning
confidence: 99%